NAPTUNE: nucleic acids and protein biomarkers testing via ultra-sensitive nucleases escalation - Tao Hu; Xinxin Ke; Yingying Yu; Hongmei Feng; Senfeng Zhang; Yinuo Cui; Boyang Zhang; Min He; Yinbing Tang; Lei Liu; Yu Lin; Quanquan Ji; et al. (Nature Communications)
Abstract In an era where swift and precise diagnostic capabilities are paramount, we introduce NAPTUNE (Nucleic acids and Protein Biomarkers Testing via Ultra-sensitive Nucleases Escalation), an innovative platform for the amplification-free detection of nucleic acids and protein biomarkers in less than 45 minutes. Using a tandem cascade of endonucleases, NAPTUNE employs apurinic/apyrimidinic endonuclease 1 (APE1) to generate DNA guides, enabling the detection of target nucleic acids at femtomolar levels. The sensitivity is elevated to attomolar levels through the action of Pyrococcus furiosus Argonaute (PfAgo), which intensifies probe cleavage, thereby boosting both sensitivity and specificity within an innovative in-situ cascade circuit. This technology not only streamlines rapid, onsite diagnostics without pre-amplification but also demonstrates exceptional accuracy in identifying a broad spectrum of nucleic acids and crucial cancer-related protein biomarkers directly from clinical samples. The development of a portable device for point-of-care testing further underscores NAPTUNE’s potential to transform diagnostic processes, especially in resource-limited environments, marking a significant diversity forward in medical diagnostics and patient care.